ResearchWave: An Ambient Visualization for Providing Awareness of Research Activities - Hinrichs, Uta; Fisher, Danyel; Henry Riche, Nathalie (Proceedings of the ACM SIGCHI conference on Designing Interactive Systems (DIS), 2010)
The goal of a research institution is, ultimately, to share and disseminate knowledge. Yet the sheer volume of expertise in such an institution makes it challenging to keep track of the vast expertise within. Even for on-site employees, knowledge of who is working on what activities is often scattered across multiple sources and media, varying in level of detail and constantly evolving over time. Acquiring this activity awareness today requires a voluntary and conscious effort from the employees. To help visitors and employees acquire and maintain a better awareness of the activities of a large research institution, we designed an ambient visualization: ResearchWave. ResearchWave addresses three distinct audiences: casual visitors, product teams and on-site researchers and takes up the challenge of representing a large amount of information in an aesthetically pleasing manner. ResearchWave is based on a “walk up and use” approach and uses multiple levels of visual encodings to engage people and stimulate more information decoding with each novel encounter. Our initial evaluations demonstrate that we achieve these goals.